Antibacterial effects of green tea extracts on Aggregatibacter actinomycetemcomitans (In-Vitro study) - Mays J Mageed; Saif S Saliem; Wifaq M Ali Alwatar (College of Dentistry/ University of Baghdad, 2015)
Background: Green Tea is made from the leaf of the plant "Camellia sinensis". Green tea is reported to contain thousands of bioactive ingredients including catechins which have shown great promise for having antimicrobial effects. Periodontal diseases represent one of the most prevalent diseases around the world and the main etiologic factor behind it, is plaque accumulation, in addition certain kinds of bacteria have been detected frequently in subjects suffering from periodontitis, Several studies suggested that the outcome of periodontal treatment is better if particular pathogens including Aggregatibacteractinomycetemcomitans can no longer be detected after therapy. Materials and Methods: plaque samples were collected from 20 patients suffering from chronic periodontitis with probing pocket depth of at least 6 mm, Aggregatibacteractinomycetemcomitans (A.A) was isolated and diagnosed according to morphological characteristics and biochemical tests. Green tea leaves were extracted by using water and alcohol. The first experiment involved testing the sensitivity of A.A to different concentrations of the extracts using agar well diffusion method,the second experiment involved determination of the minimum inhibitory concentration and then determination of the minimum bactericidal concentration of the extract against the bacteria, laboratory analysis of green tea extracts using high pressure liquid chromatography (HPLC) was performed. Results: Both green tea extracts were effective in inhibition of Aggregatibacteractinomycetemcomitans using agar well diffusion method, 90% and 100% concentrations of alcoholic extract showed larger inhibition zones than chlorhexidinegluconate 0.2% with statistically significant difference, CHX showed higher inhibition zones than all aqueous extract concentrations.The MIC (minimum inhibitory concentration) of alcoholic green tea extract that inhibit Aggregatibacteractinomycetemcomitans growth was 60%, The MIC of aqueous green tea extract that inhibits Aggregatibacteractinomycetemcomitans growth was 70%.The MBC (minimum bactericidal concentration) of alcoholic green tea extract that killsAggregatibacteractinomycetemcomitans was 80%, the MBC of aqueous green tea extract that kills Aggregatibacteractinomycetemcomitans growth was 90%. HPLC analysis of aqueous and alcoholic green tea extracts revealed that alcoholic extract contained higher concentration of EGCG while aqueous extract had higher content of catechin and epicatechin. Conclusion: Green tea extracts were effective against Aggregatibacteractinomycetemcomitans, alcoholic green tea extract showed inhibition ability more than the aqueous green tea extract and more than CHX and it showed bactericidal activity at 80%,90% and 100% concentrations.